THE FINANCIAL BEHAVIOR OF INVESTORS USING DISCRIMINANT ANALYSIS APPROACH - Juli Meliza; Isfenti Sadalia; Khaira Amalia Fachrudin (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
Behavioral finance is a recent line of research that is attracting the attention of the investor.Behavioral finance has an important role in decision-making process of investors. Thepurpose of this study is to examine whether there are any differences in the decision ofinvestors in terms of demographic variables, such as marital status, gender, education level,and then it will be examined how the different criterias on financial behavioral factorsinclude: herding, heuristics, and behavioral factors are associated with the financialmarkets. This research is descriptive quantitative. The sample in this study consists of 120stock investors in Medan. Data were collected through questionnaires, interviews, anddocumentation studies. This research applies statistical technique of discriminant analysis,using the three groups of variables: marital status, sex, and educational level. The results ofthis study showed significant differences with an alpha of 5% on financial behavioralfactors in the decision of investors in terms of marital status groups. Meanwhile, there wasno difference in the decision of investors if in terms of other demographic variables, whichconsist of sex and level of education.Keuangan perilaku cabang keilmuan yang menarik perhatian investor. Perilaku keuanganmemiliki peran penting dalam proses pengambilan keputusan investor. Tujuan daripenelitian ini adalah untuk menguji apakah ada perbedaan dalam keputusan investor dalamhal variabel demografis, seperti status perkawinan, jenis kelamin, tingkat pendidikan, dankemudian akan meneliti bagaimana kriteria yang berbeda pada faktor perilaku keuanganmeliputi: herding, heuristik, dan faktor perilaku yang terkait dengan pasar keuangan.Sampel dalam penelitian ini terdiri dari 120 investor saham di Medan. Data dikumpulkanmelalui kuesioner, wawancara, dan studi dokumentasi. Penelitian ini menggunakan teknikstatistik analisis diskriminan, dengan menggunakan tiga kelompok variabel: statusperkawinan, jenis kelamin, dan tingkat pendidikan. Hasil penelitian ini menunjukkanperbedaan yang signifikan dengan alpha 5% pada faktor-faktor perilaku keuangan dalamkeputusan investor dalam hal kelompok status perkawinan. Sementara itu, tidak adaperbedaan dalam keputusan investor pada variabel demografis lainnya, yang terdiri darijenis kelamin dan tingkat pendidikan.